Determination of heavy metals in rice (Oryza sativa L.) and soil using AuNP/BiNP/MWCNT/Nafion modified glassy carbon electrode - Tim Aren O. Salinas; Michelle T. Natividad; Shirley T. Palisoc (Heliyon, 2023)
This paper presents the fabrication and application of a gold nanoparticle (AuNP)/bismuth nanoparticle (BiNP)/multi-walled carbon nanotubes (MWCNT)/Nafion-modified glassy carbon electrode for the determination of lead (Pb) and cadmium (Cd) via anodic stripping voltammetry (ASV). The ASV parameters as well as the AuNP and BiNP contents of the electrode modifier were optimized. The surface morphology, elemental composition, and electrochemical performance of the modified electrode were characterized using scanning electron microscopy (SEM), energy-dispersive x-ray spectroscopy (EDX), and cyclic voltammetry (CV), respectively. The SEM and EDX results showed that the modifiers were present on the electrode surface, while the CV curves show the remarkable stability of the modified electrode. The limit of detection of the fabricated electrode is 2.20 ppb for cadmium and 0.58 ppb for lead. Real sample analysis was performed using rice plant parts: husk, grain, stalk, leaf, root, and soil where the rice plant was planted. The fabricated electrode was able to detect trace concentrations of Pb and Cd in the said samples.